233k views
4 votes
If a polynomial has one root in the form a+square root of 6, it has a second root in the form of a_square root of b

User Onyambu
by
4.5k points

1 Answer

1 vote

Answer:


a - √(6)

Explanation:

Polynomial is a name made of two terms: poly and nomial where poly means many and nomial means terms. Thus, polynomial can be defined as an expression that is a sum of many terms expressed different powers of same variable.

For example:
p( x) = 4x^(2) +6x +2 is an example of a polynomial.

To find roots of a polynomial, we equate p(x ) to 0 i.e.
p(x)=0.

Whenever the roots are in radical form, it implies that they will occur as conjugates.

Conjugates means that if one of the root of an equation is
a + √(b), the other root will be
a - √(b). To show that this is true and that the second root is of form
a - √(b) , we create a polynomial from the factors.

Factors are as follows:
x - (a + √(6)) and
x- (a - √(6))

Polynomial
p(x) = (x - (a + √(6))) *( x- (a - √(6)))


p(x)= x^(2) - x(a-√(6)) - x( a + √(6)) + (a+√(6))( a- √(6))


p(x)= x^(2) - 2ax + x √(6)) - x √(6)) + a^(2) - 6


p(x)= x^(2) - 2ax + a^(2) - 6

which is an quadratic equation.

Now if we try to solve this equation by using the quadratic formula we get:


x = 1/2 [ 2a + \sqrt{4 a^(2)- 4( a^(2)- 6)}] and
1/2 [ 2a - \sqrt{4 a^(2)- 4( a^(2)- 6)}]


x = a + (1/2) * √(24) and
x = a - (1/2) * √(24)


x = a + √(6) and
x = a - √(6)

Thus we get square roots of form
a + √(6) and
a - √(6).

User Vishakh
by
4.8k points